Un diagnóstico ocular complicado - Joana Antunes; Ana Batista (Galicia Clínica, 2022)
Extramedullary plasmacytoma is a rare neoplasm, corresponding to 3% of malignant plasmacyte neoplasms and 1% of all neoplasms of the head and neck. The location in the orbit is uncommon. Male patient, 71 years old, went to the emergency service due to epistaxis, temporal headache recurring for 1 month, complaints of right eye pain, and partial loss of vision. Head computed tomography was performed, which revealed a mass of soft tissues in the right orbit with an invasion of the underlying structures. After performing a biopsy of the retroocular mass and excluding the diagnosis of multiple myeloma, the diagnosis of extramedullary plasmacytoma was made. The authors considered the publication of this clinical case given the challenging diagnosis and the fact that there are few described cases of extramedullary plasmacytoma with retroocular location.